Implication of satellite images in studying potential hydrocarbon resources in the licence Blocks 9 and 11, the exclusive economic zones of Egypt and Cyprus - Rusakov, O.M.; Korchagin, I.N.; Yakymchuk, N.A.; Levashov, S.P.; Soloviev, V.D.; Bozhezha, D.N. (Геофизический журнал, 2018)
A frequency-resonance technology was used for processing and decoding the satellite images of the licence Blocks 9 and 11 in the Eastern Mediterranean. The anomalies of “oil and gas” type were revealed in the study area. The supergiant Zohr gas field produces the prominent anomaly covering the largest area of 251 km2. This anomaly evidences for the channels for vertical migration of deep hydrocarbon-bearing fluids and the horizontal gradient in reservoir pressure. For the first time, these two specific findings were suggested to be indicators of a commercial discovery. Based on them, several “oil and gas” type anomalies were recommended for exploration drilling in the Blocks 9 and 11. Available information cannot allow us to consider the Onisiforos discovery as a commercial gas field. The siliciclastic and carbonate plays are equally workable in the Egyptian, Cypriot and Israeli EEZs where in the Miocene sediments abiogenic methane is the main component of gas which ascends to reservoirs from deeper layers. Selecting an optimal drilling location requires an interdisciplinary approach. Використано частотно-резонансну технологію для обробки і декодування супутникових знімків ліцензійних блоків 9 і 11 у Східному Середземномор.ї. У досліджуваному районі виявлено аномалії типу .нафта і газ.. Супергігантське газове родовище Зохр зумовлює чітку аномалію площею 251 км2. Цій аномалії відповідає наявність каналів вертикальної міграції глибоких вуглеводневих флюїдів і горизонтальний градієнт пластового тиску в резервуарі родовища. Вперше запропоновано використовувати ці дві характерні особливості як індикатори рентабельності перспективної структури. На їх основі для розвідувального буріння було рекомендовано кілька аномалій типу .нафта і газ. у блоках 9 і 11. Наявна інформація не дає змоги розглядати перспективну структуру Онісіфор як рентабельне газове родовище. Силіцикластична і карбонатна моделі розвідувальних робіт однаковою мірою ефективні у єгипетській, кіпрській та ізраїльській ексклюзивних економічних зонах. У них абіогенний метан є основним компонентом газу, що піднімається до пасток з глибших шарів. Вибір оптимального місцеположення буріння потребує міждисциплінарного підходу.